Playing with fire [compact disc, unabridged] : a novel - Gerritsen, Tess (Brilliance Audio, 2015)
Discovering an old and strikingly unusual musical composition that causes her to black out and has a violently transformative effect on her daughter, Julia Ansdell travels to Venice to find the man behind the music and uncovers a dark secret dating back to the Holocaust.